Development of real time RT-PCR (TAQMAN) for detection and genetic characterization of antemortem human rabies - Mori, E.; Scheffer, K. C.; Fahl, W. O.; Oliveira, R. N.; Asano, K. M.; Carnieli Jr, P.; Carrieri, M. L.; Kotait, I. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Human rabies is still an important public health problem in some Brazilian regions. Usually, ante-mortem diagnosis of rabies is made by demonstration of virus antigen by direct immunofluorescence in corneal or conjunctival smears and skin biopsies; however, this technique has a low sensitivity. Recently, molecular techniques such as the reverse transcriptase polymerase chain reaction (RT-PCR) and nucleic acid sequence based amplification assay (NASBA) have been developed to improve the sensitivity and specificity of ante as well as post-mortem diagnosis of rabies. Rapid and accurate diagnosis of ante-mortem human rabies is essential for effective medical management and to ensure appropriate post-exposure prophylaxis of potential contacts with the patient. The present study was carried out to evaluate the sensitivity and specificity of real time RT-PCR (Taqman) in comparison with RT-PCR and DNA sequencing for the diagnosis of rabies. From June through July 2012, nine specimens from three patients with rabies were submitted to the Pasteur Institute for rabies diagnosis. Five saliva (2551 and 2613 to 2616) and two hair follicles (2552 and 2612) specimens were collected serially from patient suspected of having rabies from Mato Grosso (MT) state. Saliva (3550 and 4109) specimens were collected from patients rabies suspected from Minas Gerais (MG) and Maranhao (MA) states, respectively. The positive rabies results were confirmed by RT-PCR using primers targeted to nucleoprotein (N) gene and all of specimens were identified as compatible with hematophagous bat lineage (variant 3) by DNA sequencing, with the exception of the saliva collected from MA patient, which was genotyped as canid lineage (variant 2). A real time RT-PCR (Taqman), with two primers and probe sets targeting to N, has been described in order to validate an alternative method for rabies diagnosis in ante-mortem samples. This method was capable of accurately identifying the variant 3 in saliva specimens collected from MT patient previously genotyped as hematophagous bat lineage. The hair follicle and saliva specimens from MT and MG patients, respectively, yielded high Ct (threshold cycle) values (between 35 and 38), suggesting low viral load. This assay failed to detect amplification in the challenge virus standard (CVS) strain and saliva collected from MA patient (genotyped as variant 2) due to mismatches between the primers/probe sets and the target N gene. Thus, our results showed the usefulness of real time RT-PCR as a rapid alternative to DNA sequencing (at least four times faster) for the confirmation of rabies diagnosis.